Assembly of MnCO3 nanoplatelets synthesized at low temperature on graphene to achieve anode materials with high rate performance for lithium-ion batteries. (10th October 2016) - Wang, Kang; Shi, Yan-Hong; Li, Huan-Huan; Wang, Hai-Feng; Li, Xiao-Ying; Sun, Hai-Zhu; Wu, Xing-Long; Xie, Hai-Ming; Zhang, Jing-Ping; Wang, Jia-Wei
Graphical abstract: A novel kind of MnCO3 nanoplatelets-reduced graphene oxide (RGO) composite was prepared by a simple low temperature reaction route which presented improved rate performance. Abstract: A novel kind of MnCO3 nanoplatelets-reduced graphene oxide (RGO) composites, as an anode material in rechargeable Li-ion battery, was prepared by a simple low temperature reaction route. The graphene not only provided an avenue for the transport of Li-ion, but also buffered the volume expansion of MnCO3 nanoplatelets during charge and discharge. Compared to pure MnCO3 nanoplatelets, MnCO3 -RGO composites presented the improved electrochemical performances. At a low current density of 100 mA g −1, MnCO3 -RGO composites delivered a desired performance of 849.1 mAh g −1 after 200 cycles. When at a high current density of 500 mA g −1, the discharge capacity still maintained at 810.9 mAh g −1 after 700 cycles. Our experimental results suggest that this composite will be a candidate as a novel anode material for the power batteries of electric vehicles and the energy storage batteries of smart grids in the future.